The Impact of School Choice on Public School Budgets: Evidence From Open Enrollment in New York City. (9th July 2020) - Rothbart, Michah W.
Abstract : This paper examines budgetary responses of public schools to competition from school choice, exploiting a discrete change in the choice set available to New York City high school students in 2003–2004. Schools facing increased competition (zoned, unscreened, and those with few applicants) increase per‐pupil expenditures on noninstructional functions, reducing resources for instruction. Thus, schools may face important tradeoffs when competing for applicants, including between quantity and academic quality of applicants and between incentives to reach capacity and to improve academic outcomes. While advocates claim that school choice improves academic achievement, these results may help explain mixed findings in the previous literature.